Two Novel Loci of RELN Associated With Antipsychotics Response in Chinese Han Population - Xu, Qingqing; Li, Mo; Qin, Shengying; Li, Yaojing; Ning, Ailing; Fu, Yingmei; Wang, Dongxiang; Zeng, Duan; Li, Huafang; Yu, Wenjuan; Yu, Shunying (Frontiers in Pharmacology, 2020)
Background There are great individual differences in the drug responses; however, there are few prognostic drug response biomarkers available. RELN is one of the more extensively examined schizophrenia candidate genes. The purpose of this study was to determine whether RELN can affect antipsychotics response in the Chinese population. This may lead to the discovery of relevant novel drug response markers. Methods The unrelated 260 Chinese Han inpatients with schizophrenia were enrolled in the present study. The enrolled subjects have been prescribed antipsychotic medication during the study. A total of 15 SNPs of RELN were genotyped by MassARRAY® platform. The association of the RELN gene with therapeutic response to antipsychotics was analyzed based on sex and age at onset. Results Two novel SNPs of RELN were found to be associated with antipsychotic treatment response (rs155333, p = 0.010 and rs6465938, p = 0.049) at nominal significance threshold, but not after multiple correction. Our study also revealed highly significant association of a haplotype consisting of three SNPs (rs362814-rs362626-rs2237628) with antipsychotic treatment response. Even after permutation, the p-value indicated significant association (rs362814-rs362626-rs2237628: ACT, χ2 = 6.353, p = 0.0117, permuted p = 0.04). Furthermore, a novel SNP, rs2535764, was found to be associated with antipsychotic response under overdominant genetic model at a marginal significant level of 0.046 (C/T vs. C/C + T/T: p = 0.046, AIC = 314.7, BIC = 321.6). Conclusion Our data indicated that RELN can affect antipsychotic treatment outcomes in the Chinese population. SNPs of RELN could be used as predictive biomarkers for future personalized medicine of antipsychotic drug treatment. However, none of the three novel SNPs (rs155333, rs6465938, and rs2535764) remained significant after Bonferroni correction. Therefore, validation is needed in larger pharmacogenetic studies.